Risk of Suicide Attempt in Patients With Recent Diagnosis of Mild Cognitive Impairment or Dementia - Günak, Mia Maria; Barnes, Deborah E; Yaffe, Kristine; Li, Yixia; Byers, Amy L (JAMA psychiatry (Chicago, Ill.), 2021)
Little is known about the association between mild cognitive impairment (MCI) and suicide. Most studies have focused on dementia and suicidal behavior, with inconsistent results. To examine the association between diagnoses of MCI and dementia and suicide attempt and explore potential psychiatric moderators and to assess whether the association differs based on recency of diagnosis. This nationwide cohort study integrated 5 national databases from the Department of Veterans Affairs (VA) and Centers for Medicare & Medicaid Services and included all VA medical centers in the US. US veterans 50 years or older with MCI diagnoses at baseline (October 1, 2011, to September 30, 2013) or earlier (October 1, 2007, to September 30, 2011) were propensity matched 1:3 with (1) patients with dementia diagnoses and (2) patients without either diagnosis based on demographic characteristics and the Charlson Comorbidity Index. Diagnoses of MCI or dementia were defined as recent if there were no diagnosis codes before baseline. Data were analyzed from March 16, 2020, to January 15, 2021. Information on suicide attempts through December 31, 2016, provided by the National Suicide Prevention Applications Network (nonfatal) and Mortality Data Repository (fatal). The study population of 147 595 participants included 21 085 patients with MCI, 63 255 with dementia, and 63 255 in the propensity-matched comparison group. Participants had a mean (SD) age of 74.7 (10.3) years, 143 353 (97.1%) were men, 4242 (2.9%) were women, and 127 065 (86.1%) were non-Hispanic White. A total of 138 patients with MCI (0.7%) and 400 patients with dementia (0.6%) attempted suicide during follow-up, compared with 253 patients without MCI or dementia (0.4%). Exploratory analyses revealed that no psychiatric comorbidity moderated the association between MCI or dementia and suicide attempt. After adjustment for demographic details and medical and psychiatric comorbidities, risk of suicide attempt was consistently highest for patients with a recent MCI or dementia diagnosis, with adjusted hazard ratios (HRs) of 1.73 (95% CI, 1.34-2.22; P < .001) for recent MCI and 1.44 (95% CI, 1.17-1.77; P = .001) for recent dementia. Risk associated with prior diagnosis was not significant (HR for prior MCI, 1.03 [95% CI, 0.78-1.36; P = .84]; HR for prior dementia, 1.14 [95% CI, 0.95-1.36; P = .15]). This study found that older adults with recent MCI or dementia diagnoses were at increased risk of attempting suicide. These findings suggest that involvement of supportive services at the time of or soon after diagnoses of MCI or dementia may help mitigate risk of suicide attempts.